PARTISIPASI MASYARAKAT DALAM USAHA PENGELOLAAN EKOWISATA DI HUTAN MANGROVE TAPAK, KECAMATAN TUGUREJO, KOTA SEMARANG - Chriestian, Chriestian; Trenggono, Trenggono (Media Bina Ilmiah, 2024)
Mangrove ecotourism is one of the mangrove forest tourism managed by various stakeholders as an effort to save coastal ecosystems in Semarang City. It is known that 90% of mangrove forests on the north coast of Java, including Semarang have been damaged, while mangrove forest ecosystems have an important role for the sustainability of coastal areas. To realize the goals of ecotourism, the role and involvement of the community is needed. For this reason, the participation and understanding of local communities in participating in managing mangrove ecotourism is very important to know. This study aims to determine the management system and local community participation and the factors that encourage it. This research method is qualitative and data collection is done through observation, interviews, and literature study. The results of the study show that coordination between managers is less than optimal, and community participation is good but not distribute well